The Da’wah Strategy of the Indonesian Mosque Youth and Adolescent Communication Body Organization in Addressing Inter-Youth Brawls in Tanjung Morawa District - Khafifa Inda Syahrani; Muktarruddin Muktarruddin (Madania: Jurnal Ilmu-Ilmu Keislaman, 2026)
Youth brawls represent a persistent social problem that reflects broader issues related to unstructured leisure time, weak social supervision, and negative peer influence. This study aims to analyze mentoring strategies implemented to anticipate and reduce youth brawls through a community-based and value-oriented approach. Employing a qualitative field research design, data were collected through in-depth interviews with anonymized informants and supported by documentation. The data were analyzed using an interactive qualitative analysis model involving data reduction, data display, and conclusion drawing, with trustworthiness ensured through source, technique, and time triangulation. The findings reveal that preventive strategies centered on positive collective activities, dialogical counseling, and leadership development play a significant role in redirecting adolescents away from risky nighttime behaviors. Rather than relying on punitive measures, the approach emphasizes behavioral substitution, value internalization, and youth empowerment. Verbatim-based analysis indicates a shift in adolescents’ self-perception, sense of purpose, and social belonging, which contributes to a decline in conflict-prone activities. Leadership training further supports the sustainability of behavioral change by positioning adolescents as active agents within their peer groups. This study contributes to the field of community-based mentoring and da’wah management by demonstrating that contextual, participatory strategies can effectively address recurring youth social problems. The findings offer practical implications for stakeholders in designing preventive youth development programs grounded in local social realities.